1998
DOI: 10.1073/pnas.95.6.3193
|View full text |Cite
|
Sign up to set email alerts
|

Verbal novelty detection within the human hippocampus proper

Abstract: Animal studies and neuropsychological tests of patients with temporal lobe epilepsy have demonstrated the importance of human medial temporal lobes for memory formation. In addition, more recent studies have shown that the human hippocampal region is also involved in novelty detection. However, the exact contribution of the hippocampus proper to these processes is still unknown. To examine further its role we compared event-related potentials recorded within the medial temporal lobes in 29 temporal lobe epilep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
124
0
4

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(138 citation statements)
references
References 45 publications
10
124
0
4
Order By: Relevance
“…As mentioned earlier, we selected the seed voxels for our analysis in the hippocampus because of considerable evidence in the literature about the involvement of the hippocampus in novelty detection [1,2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]47]. It is also generally accepted that novelty detection involves regions beyond the hippocampus [ 1,2,12,17,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, we selected the seed voxels for our analysis in the hippocampus because of considerable evidence in the literature about the involvement of the hippocampus in novelty detection [1,2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]47]. It is also generally accepted that novelty detection involves regions beyond the hippocampus [ 1,2,12,17,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Novelty/familiarity discrimination (also known as novelty detection, or novelty assessment) is useful for the organism in a variety of situations, can take a number of specific forms, and can serve several functions (see reviews by [1][2][3][4]). The hippocampal system has been found to be critically involved in many tasks involving neural novelty/familiarity (henceforth just 'novelty') discrimination [1,2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In this report, we describe a positron emission tomography (PET) study whose purpose was to explore the idea that novelty discrimination does not depend on the hippocampal system alone but is subserved by large-scale neuronal networks which include but go beyond the hippocampal system.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that the relationship between hippocampal (and parahippocampal) activity and continuous psychological dimensions, such as item novelty, cannot be captured by a unitary function. Keywords novelty; familiarity; hippocampus; fMRI; high-resolution Consistent with human and animal lesion data implicating MTL in recognition memory (for reviews, see Brown & Aggleton, 2001;Eichenbaum et al, 2007;Squire et al, 2007), fMRI and intracranial (local field potential and single-neuron) recording studies have demonstrated that hippocampal activity is modulated by the study status of recognition test items (e.g., Grunwald et al, 1998;Heit et al, 1988; for a review of fMRI findings, see Henson, 2005). Among event-related fMRI studies employing separate study and test phases, it has occasionally been reported that correctly-recognized (old) items elicit greater hippocampal activity than correctly-rejected (new) items (e.g., Donaldson et al, 2001;Stark & Squire, 2001).…”
Section: Introductionmentioning
confidence: 89%
“…stimuli, a frontal/central P300 can be elicited with a relatively short peak latency that habituates rapidly (Courchesne et al, 1975;Knight, 1984). This potential has been called the "novelty P300" and is interpreted as reflecting frontal lobe activity related to the hippocampus (Grunwald et al, 1998;Knight, 1996). It is observed across modalities (Fabiani et al, 1998;Yamaguchi and Knight, 1991) and populations Knight, 1987;Yamaguchi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%